Effect of organic fertilizers sources and level of mineral fertilizers in total tuber yield and concentration of N, P and K in tuber of potato (Solonum tuberosum L.) - AL-Fadlay, Jawad Taha Mahmood; AL- Khadimy, Naddin Aziz Salman (Journal of Kerbala for Agricultural Sciences, 2018)
To investigate the effects of manure (plants residue) on growth and yield of potato in calcareous soil, afield experiment were conducted in field located in physical education college areas Baghdad University – Jadiriyah campus in fall season 2015-2016 in a sandy loam soil, Included two factors first factor is four serous of manure O0 (without application) O1( poultry) O3( wheat straw) O3 (palm fronds) with 30 Ton h-1, Second factor application three level of mineral fertilizers (without application) M0 (120 N + 60 P + 200 K ) M1 (240 N + 120 P + 400 K ) Kg h-1 layout in ( RCBD) with three replication, manures and phosphate fertilizer were added two week per planting, seed of potatoes class (Desiree) planted on 22 September 2015, adding nitrogen and potassium fertilizer in three equal 21,45 and 70 days after planting, on 22 January 2016 at maturity stage, tubers from five plants in each medium rows harvested to determine total tuber yield, concentration of N, P and k in dry mass tubers were determined, Results showed a superiority treatment of poultry gave 49.94 Ton h-1 and highest concentration of N 2.06%, P 0.32% and 2.66% K, M2 treatment gave highest total tuber yield 50.20 Ton h-1 and 2.05 % N, 0.36% P and 2.54% K. interaction treatment M2O2 gave 57.22 Ton h-1 total tuber yields and 2.19%, 0.39% and 2.57% concentration of N, P and K in tubers respectively